Latin America and Europe face to global changes - Rojas Aravena, Francisco (2013)
This article refers to the weakening of the international system due to the various global changes that have occurred in recent years. In addition, the author argues traditional concepts of Social Sciences and International Relations have changed because of power relations, especially concepts related to time and space currently global and simultaneous. Finally, concludes that some tendencies will affect Latin America and the European Union regarding globalization, peace, consolidation of the democratic system, summit diplomacy, cooperation and power as a changing element.